Targeting Synaptic Plasticity in Experimental Models of Alzheimer’s Disease - Mango, Dalila; Saidi, Amira; Cisale, Giusy Ylenia; Feligioni, Marco; Corbo, Massimo; Nisticò, Robert (Frontiers in Pharmacology, 2019)
Long-term potentiation (LTP) and Long-term depression (LTD) of hippocampal synaptic transmission represent the principal experimental models underlying learning and memory. Alterations of synaptic plasticity are observed in several neurodegenerative disorders including Alzheimer’s disease (AD). Indeed, synaptic dysfunction is an early event in AD, making it an attractive therapeutic target for pharmaceutical intervention. To date, intensive investigations have characterized hippocampal synaptic transmission, LTP and LTD in in vitro and in murine models of AD. In this review we describe the synaptic alterations across the main AD models generated so far. We then examine the clinical perspective of LTP/LTD studies and discuss the limitations of non-clinical models and how to improve their predictive validity in the drug discovery process.